Pharmacists’ insights and behaviors in preventing the misuse of topical corticosteroids in Pakistan: a mixed-method study - Shakeel, Sadia; Nesar, Shagufta; Iffat, Wajiha; Rehman, Hina; Aziz, Samreen; Mumtaz, Tayyaba; Ab. Hadi, Hazrina; Jamshed, Shazia (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Topical corticosteroids (TCs) misuse has become a common issue for healthcare profession- als and patients, particularly in Pakistan, as no stringent laws or rules are prohibiting the selling of over-the-counter medicines. The present study was designed to examine pharmacists’ insights and behaviors regarding TCs and their potential role in preventing the misuse of TCs in Pakistan. The study was a cross-sectional mixed-methods research design (phase 1, quantitative; and phase 2, qualitative) conducted from January to June 2021. The pharmacists working in various settings in Karachi were approached through different social media platforms. Data were collected through a web link of an online questionnaire with 30 closed-ended questions. Different statistical methods were employed for tabulating the quantitative data, while inductive thematic analysis was directed to classify themes from the qualitative data and to conclude findings. The mean cumulative knowledge score was 10.59 ± 1.63. The community pharmacists knew more about the available over-the-counter TCs (p = 0.041). The experienced pharmacists were more conversant than fresh pharmacists, regard- ing the mode of action (p = 0.008), choice of TC potency (p = 0.001), and most common local and systemic adverse effects of TCs (p = 0.001). Overall, respondents had a favorable attitude, with more than 80% agreeing that pharmacists could ensure that important safety issues are communicated with patients, and assist considerably in avoiding TC misuse. Analysis of data has produced 7 themes, 10 sub-themes, and 30 categories. Major themes included: use and misuse of TCs, adverse drug events due to TCs, cosmeto-vigilance, patient education, referral to a physician, and future perspectives for preventing TC misuse. The respondents were well versed with the dilemma of TCs misuse, and they considered patient characteristics, free availability of TCs, and lack of physician-pharmacist coordination as the major reasons. The major barriers for patient education stated by nearly all the respondents were a lack of time and lack of material/information for counseling. They emphasized the need for stringent legal strategies and the enforcement of current drug-control regulations, so that TCs are not supplied without appropriate prescriptions. The present findings indicate that pharma- cists had appropriate knowledge and a positive attitude towards their potential role in preventing the misuse of TCs. Further education and sensitization in areas of deprived knowledge will undoubtedly aid in the prevention of TCs misuse by the community.